Influence of macro- versus microcooling on the physiological and psychological performance of the human operator - Heyns, Gerhardus Johannes (Rhodes University, Faculty of Science, Department of Human Movement Studies, 1995)
This study evaluated the effect of a macro- versus a microcooling system on the cognitive, psychomotor and physiological performance of human operators. Male subjects (n = 24) were acclimatized for four days and then subjected to three different environmental conditions: hot ambient (40Â°C; 40% RH), microcooling and macrocooling. Each environmental condition was repeated twice; once under a rest condition and once while simulating a physical workload of 40 W. Four performance tests (reasoning, eye-hand coordination, memory, reaction time) were conducted once every hour for four hours. Five physiological measurements, viz rectal temperature, skin temperature, heart rate, total sweat loss and sweat rate, were taken. A significant difference existed between the physiological responses under the hot ambient condition and both cooling conditions. For all five physiological parameters he human operator benefitted substantially whatever the cooling condition. The psychological performance results indicated a greater benefit under the cooling conditions, though various external factors may have influenced responses. User perception showed that macrocooling was perceived to be the optimal method of cooling. The results showed that there was no difference in the extent to which both rectal temperature and heart rate (for rest and work conditions) decreased over the 4-hour study period with micro- and macrocooling. In the baseline hot environment both increase. Sweat rate was lowest when resting or working in a microcooled environment and at its highest in the hot baseline environment. Mean skin temperature was lowest (for rest and work conditions) with microcooling and highest in the hot baseline environment. Reaction time and memory/attention were the same under all three environmental conditions. Eye-hand coordination was better with cooling than without, but did not differ between the two cooling conditions. Reasoning ability was poorest under the hot baseline condition and best in the macrocooled environment. User perception showed that the subjects found macrocooling highly acceptable. Microcooling was found to be uncomfortable, particularly because cold air (18 - 21Â°C) entered the jacket at one point which caused numbness of the skin at that point. Jackets did not always fit subjects well and the umbilical cord restricted free movement.
Keywords: Cold -- Physiological effect; Temperature -- Physiological effect; Body temperature -- Regulation; Heat -- Physiological effect